1996
DOI: 10.2136/sssaj1996.03615995006000050037x
|View full text |Cite
|
Sign up to set email alerts
|

Recently Deposited Organic Matter in Soil Water‐Stable Aggregates

Abstract: Some suggest that young labile soil organic matter accumulates preferentially in water‐stable macroaggregates (>250 µm) where it acts as a transient binding agent. We determined the proportions of recently deposited C (<15 yr) in water‐stable aggregate size fractions using 13C natural abundance. The experiment was performed on a silty loam (fine‐loamy, mixed, frigid Aeric Haplaquept) on plots that were under either continuous corn (C4) or a mixed C4‐C3 rotation for 15 yr and that had previously been unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
57
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(71 citation statements)
references
References 0 publications
14
57
0
Order By: Relevance
“…This suggests that OM in microaggregates was less mineralizable than that in macroaggregates. This supports other findings on Gleysol from Eastern Canada, which showed that OM associated with microaggregates had a slower turnover rate and is more processed than that associated with macroaggregates (Angers and Giroux 1996;Monreal et al 1997).…”
Section: Resultssupporting
confidence: 90%
“…This suggests that OM in microaggregates was less mineralizable than that in macroaggregates. This supports other findings on Gleysol from Eastern Canada, which showed that OM associated with microaggregates had a slower turnover rate and is more processed than that associated with macroaggregates (Angers and Giroux 1996;Monreal et al 1997).…”
Section: Resultssupporting
confidence: 90%
“…10), based on the concepts presented in Figure 2 and additional data collected, specific to NT and CT systems. According to the model, fresh plant material provides the POM that acts as a nucleation site for the growth of fungi and other soil microbes [5,150,209]. Microbial growth and the resulting production of extracellular polysaccharides bind residue and soil particles into macroaggregates.…”
Section: Mechanisms Of C Sequestration Under No-tillagementioning
confidence: 99%
“…Water-stable aggregation (WSA) is often used as an index of soil quality and can serve as an indicator of a soil's resistance to water and wind erosion (Angers et al 2008). Nonetheless, although much research has been conducted on the dynamics of SOM fractions (e.g., Six et al 1999;Lal 2004) and their relationships with WSA (e.g., Angers and Giroux 1996;Chenu et al 2000), little is known about SOM and WSA recovery with time on eroded soils and their relationships with soil resilience and resistance. Similarly, the legacy effect of amendments (manure and fertilizer) applied to eroded surfaces has not been quantified.…”
Section: Introductionmentioning
confidence: 99%